Correlations of condition factor and gonadosomatic, hepatosomatic and lipo-somatic relations of Leptodactylus macrosternum (ANURA: Leptodactylidae) in the Brazilian Semi-arid - MARCIO F. CHAVES (Anais da Academia Brasileira de Ciências, 2017)
The objective of this study was to assess variations of the condition factor (K1) in relation to the gonadosomatic- RGS and energy reserves (hepatosomatic - RWL and liposomatic – RFB relations) of Leptodactylus macrosternum and their relationship to climate variation in the Northeast of Brazil, Caatinga area, state of Paraiba. The animals were captured fortnightly through active collecting, between January and December 2013. Significant differences were observed in the monthly variations of K1, RGS and RFB indices in male and female L. macrosternum over the months of collection. In males, K1 showed no significant relationship with the other variables. In females, RGS values only show notable correlations with RWF and K1 values. K1 values showed significant correlations with all other weight and length ratios. Climate change in the HFOB region showed significant relationships with the variation of the indexes evaluated, with the exception of RWF. The variation of K1, RGS, RWL and RFB values over the months of collection as well as their relation with the local climatic variation, showed a brief reproductive activity for the species.